PEGylated liposomes associate with Wnt3A protein and expand putative stem cells in human bone marrow populations. (April 2017) - Janeczek, Agnieszka A; Scarpa, Edoardo; Horrocks, Mathew H; Tare, Rahul S; Rowland, Caroline A; Jenner, Dominic; Newman, Tracey A; Oreffo, Richard OC; Lee, Steven F; Evans, Nicholas D
Aim: To fabricate PEGylated liposomes which preserve the activity of hydrophobic Wnt3A protein, and to demonstrate their efficacy in promoting expansion of osteoprogenitors from human bone marrow.Methods: PEGylated liposomes composed of several synthetic lipids were tested for their ability to preserve Wnt3A activity in reporter and differentiation assays. Single-molecule microspectroscopy was used to test for direct association of protein with liposomes.Results: Labeled Wnt3A protein directly associated with all tested liposome preparations. However, Wnt3A activity was preserved or enhanced in PEGylated 1, 2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) liposomes but not in PEGylated 1, 2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) liposomes. PEGylated Wnt3A liposomes associated with skeletal stem cell populations in human bone marrow and promoted osteogenesis.Conclusion: Active Wnt protein-containing PEGylated liposomes may have utility for systemic administration for bone repair.